Impact of small business management on optimizing business performance (Study on small-scale cake businesses in Sarolangun District) - Candra Mustika; Sigit Indrawijaya; Zamzami Zamzami (Jurnal Perspektif Pembiayaan dan Pembangunan Daerah, 2018)
The purpose of this research is to analyze the corporate governance of Small and Medium-sized Enterprises (SMEs) in Creative Industry from the aspect of industrial profile, financial management, human resources management, operational management and marketing management in Sarolangun District. The population in this study was a group of Small and Medium Industries in Sarolangun District. This study examined 100 companies belonging to the SMEs. Primary data collection is carried out using questioner instrument and Focus Group Discussion techniques by involving stakeholders including business actors, government, academics and consumers. Descriptive analysis approach and statistical analysis/verification also used in this study. SWOT analysis is used for quantitative approach on the other hand matrix were used for qualitative approaches. The weighting and categorization of the results of the research variables suggests that financial management is in good category, marketing management is in good category, human resource management is in good category, operational management is not in good category and lastly business performance is in good category. The results of the SWOT diagram prove that the management position of the small-scale cake maker in Sarolangun District is currently in quadrant I, meaning that small-scale cake-making businesses in Sarolangun District already have the power and opportunity to improve business performance, thus the right strategy to improve the current business performance is through aggressive strategy.